Knowledge, perception and expectation of nurses towards pharmacists’ roles in pharmaceutical care: a pilot study in private outpatient haemodialysis centres in Kuantan, Malaysia - Mahdzir, Zulhasri; Mohamed Nazar, Nor Ilyani; Mohamad Noor, Zaswiza (UniKL Royal College of Medicine Perak, 2022)
Introduction: The aim of this study was to assess and evaluate nurses' knowledge, perception, and expectation regarding the potential roles of pharmacists in pharmaceutical care at private outpatient haemodialysis centres. Methods: A descriptive, cross-sectional study was conducted among nurses who were working in private outpatient haemodialysis centres in Kuantan. Sociodemographic data and parameters measuring nurses' knowledge, perception, and expectation on the potential roles of pharmacist in the centres, were collected using a validated questionnaire distributed by a researcher at the study settings. The nurses gave their consent to participate, and a researcher was present at the centre to assist them fill in the questionnaire. Data was analysed using SPSS. Results: A total of 63 nurses from 11 centres participated in this study. The results showed that 52.4% of them had adequate knowledge on the potential roles of pharmacist in outpatient dialysis centres. The majority of the nurses agreed or strongly agreed (84%) that pharmacists are reliable as the source for general and clinical drug information. At least 50.8% of them expected pharmacists to resolve drug-related problems at dialysis centre. Conclusion: This study found that the nurses expressed adequate level of knowledge, perception, and expectation on the potential roles of pharmacists in outpatient dialysis centres. A majority of them had a positive perception on pharmacists in expanding pharmaceutical services in the outpatient dialysis centres.